A new deep-water species of Odontozona (Decapoda: Stenopodidea: Stenopodidae) from the East Pacific, and new record of O. foresti Hendrickx, 2002 - Hendrickx, Michel E.; Ayón-Parente, Manuel (Zootaxa, 2014)
A new species of the stenopodid shrimp Odontozona is described from deep-water off the west coast of Mexico. It is distinguished from the three other species of the genus known in the area, from O. rubra Wicksten, 1982, and O. foresti Hendrickx, 2002, by the absence of a series of spines on the posterior half of the carapace, behind the post-cervical groove, and from O. spongicola (Alcock & Anderson, 1899) by the presence of spines on the ventral margin of somites 1–5 (smooth in O. spongicola) and by the much slender third pair of pereiopods in the new species. A new record is provided for O. foresti, and the first male specimen, the third specimen on record, is compared with the female holotype.